CARDI Factsheets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
CARDI (Caribbean Agricultural Research and Development Institute) has produced a small booklet listing the titles of the Institute's Factsheets and Bulletins. Factsheets were produced and directed to extension officers and were well received by...